2018
DOI: 10.3390/biomedicines6020058
|View full text |Cite
|
Sign up to set email alerts
|

The Crosstalk of Endoplasmic Reticulum (ER) Stress Pathways with NF-κB: Complex Mechanisms Relevant for Cancer, Inflammation and Infection

Abstract: Stressful conditions occuring during cancer, inflammation or infection activate adaptive responses that are controlled by the unfolded protein response (UPR) and the nuclear factor of kappa light polypeptide gene enhancer in B-cells (NF-κB) signaling pathway. These systems can be triggered by chemical compounds but also by cytokines, toll-like receptor ligands, nucleic acids, lipids, bacteria and viruses. Despite representing unique signaling cascades, new data indicate that the UPR and NF-κB pathways converge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 108 publications
(133 reference statements)
2
92
0
Order By: Relevance
“…UPR signalling cascades act through the three main ER stress sensor proteins, PERK, IRE1 and ATF6 . It has been known that NF‐κB is critically involved in the inflammatory response within the complex signalling pathways during UPR . Phosphorylation of PERK and IRE1 by ER stress has been linked to downstream NF‐κB activation and subsequent pro‐inflammatory gene transcription .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UPR signalling cascades act through the three main ER stress sensor proteins, PERK, IRE1 and ATF6 . It has been known that NF‐κB is critically involved in the inflammatory response within the complex signalling pathways during UPR . Phosphorylation of PERK and IRE1 by ER stress has been linked to downstream NF‐κB activation and subsequent pro‐inflammatory gene transcription .…”
Section: Discussionmentioning
confidence: 99%
“…35,36 It has been known that NF-κB is critically involved in the inflammatory response within the complex signalling pathways during UPR. 37,38 Phosphorylation of PERK and IRE1 by ER stress has been linked to downstream NF-κB activation and subsequent pro-inflammatory gene transcription. 39 Data from the time-course study revealed that the expression of p-PERK and p-IRE1 was also enhanced during the development of VPN, and was basically correlated to the expression of NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study revealed that the application of the NF-κB inhibitor BAY 11-7082 enhanced epithelial apoptosis in experimental colitis 20 , suggesting a role for activated NF-κB in inhibiting apoptosis. Moreover, growing evidence has indicated that NF-κB is involved in the regulation of ER stress signaling and ferroptosis process 21,22 . However, the definite protective mechanisms of NF-κB via the regulation of ER stress-mediated ferroptosis in UC are not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, endoplasmic reticulum stress-coupled inflammation plays an important role in the occurrence and development of diabetic atherosclerosis. It has been found that insulin resistance can make macrophages more sensitive to endoplasmic reticulum stress-mediated apoptosis, induce inflammation, macrophage and smooth muscle cell apoptosis, and promote atherosclerosis occurrence and development [16][17]. Antioxidant enzyme system is an important barrier for the body's antioxidant injury, which mainly includes GSH-Px, SOD.…”
Section: Discussionmentioning
confidence: 99%